2015
DOI: 10.1104/pp.15.00325
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone Regulates Leaf Senescence in Concert with Ethylene in Arabidopsis

Abstract: Leaf senescence is not a passive degenerative process; it represents a process of nutrient relocation, in which materials are salvaged for growth at a later stage or to produce the next generation. Leaf senescence is regulated by various factors, such as darkness, stress, aging, and phytohormones. Strigolactone is a recently identified phytohormone, and it has multiple functions in plant development, including repression of branching. Although strigolactone is implicated in the regulation of leaf senescence, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
170
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(183 citation statements)
references
References 60 publications
8
170
0
5
Order By: Relevance
“…Strigolactones are produced in two forms (as endogenous hormones and root secretions). Strigolactones are involved in various roles like promoting symbiotic interactions (arbuscular mycorrhizal fungi) (Evangelisti et al, 2014); enhancing cell elongation within the root but inhibiting root hairs and asymmetric root growth ; affecting developmental processes (Yoneyama et al, 2013), involving in light harvesting mechanism (Mayzlish-Gati et al, 2010) and leaf senescence (Woo et al, 2001); performing cross-talk with other major hormones like auxin, ABA and ethylene ; controlling leaf shape, lamina joint inclination and tiller angle (Sang, 2014); delaying leaf senescence and reducing secondary growth and controlling PCD (Programmed cell death), photomorphogenesis and modulating biotic/abiotic stress responses (Xiong et al, 2014;Ha et al, 2014;Ueda and Kusaba, 2015). Strigolactones are widely distributed and GR24 is its synthetic analogue (Gomez-Roldan et al, 2008;Tsuchiya and McCourt, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Strigolactones are produced in two forms (as endogenous hormones and root secretions). Strigolactones are involved in various roles like promoting symbiotic interactions (arbuscular mycorrhizal fungi) (Evangelisti et al, 2014); enhancing cell elongation within the root but inhibiting root hairs and asymmetric root growth ; affecting developmental processes (Yoneyama et al, 2013), involving in light harvesting mechanism (Mayzlish-Gati et al, 2010) and leaf senescence (Woo et al, 2001); performing cross-talk with other major hormones like auxin, ABA and ethylene ; controlling leaf shape, lamina joint inclination and tiller angle (Sang, 2014); delaying leaf senescence and reducing secondary growth and controlling PCD (Programmed cell death), photomorphogenesis and modulating biotic/abiotic stress responses (Xiong et al, 2014;Ha et al, 2014;Ueda and Kusaba, 2015). Strigolactones are widely distributed and GR24 is its synthetic analogue (Gomez-Roldan et al, 2008;Tsuchiya and McCourt, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, SLs or their further metabolites were shown to be a novel class of plant hormone inhibiting shoot branching. 10,11) These findings attracted researchers to study the biological functions of SLs and they have been shown to be involved in the regulation of growth of lateral roots and root hairs, 12,13) secondary growth, 14) photomorophogenesis 15) and leaf senescence, 16,17) and to promote root colonization by root nodule bacteria. [18][19][20][21] Approximately 25 natural SLs have been characterized from root exudates of various plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Pea, Arabidopsis, rice and petunia mutants with defects in SL biosynthesis or SL responses were first identified based on their increased shoot branching phenotypes and their dwarfism (Beveridge et al, 1996;Ishikawa et al, 2005;Napoli, 1996;Stirnberg et al, 2002). Less obvious phenotypes, such as reduced secondary growth, delay in leaf senescence or modified root architecture, were later identified (Brewer et al, 2013;Ueda and Kusaba, 2015;Yamada et al, 2014). SLs can also modulate tolerance to abiotic stresses (drought) (Ha et al, 2014).…”
Section: Key Developmental Roles For Sl Signalingmentioning
confidence: 99%